Fruit – sustaining life in the forest - Jutta, Mariam (University Putra Malaysia, 2012)
Fruit are very important for the survival of animals. In Malaysian forests members of the mulberry family or Moraceae play a crucial role as year-round food sources. Prominent are Ficus (figs) and Artocarpus (e.g. cempedak, terap), with about 100 and 20 species respectively. Despite a milky, often irritant sap most have edible, usually pulpy or juicy fruit, and many are common species in our forests. Most are “pioneer species”, i.e. among the first species to establish in a disturbed area, e.g. a gap in the canopy due to an old tree toppling over or after a landslide